2020
DOI: 10.3390/ma13061409
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Concentration Hydrofluoric Acid Etching on Shear Bond Strength and Biaxial Flexural Strength after Thermocycling

Abstract: This study evaluated the shear bond strength (SBS) and biaxial flexural strength (BFS) of resin cements according to the surface treatment method using low-temperature hot etching with hydrofluoric acid (HF) on a yttrium-stabilized tetragonal zirconia (Y-TZP) surface; 96 discs and 72 cubes for BFS and SBS tests for Y-TZP were randomly divided into four groups of BFS and three groups of SBS. Specimens were subjected to the following surface treatments: (1) no treatment (C), (2) air abrasion with 50 μm Al2O3 par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…HE specimens showed significantly higher SBS values than SB or CT specimens ( p < 0.05). These results are consistent with the findings of Kang et al [ 32 ]. With Maxcem Elite, HE specimens showed a markedly (810%) higher adhesive strength than CT specimens, as well as a 105% higher adhesive strength than SB specimens.…”
Section: Discussionsupporting
confidence: 94%
“…HE specimens showed significantly higher SBS values than SB or CT specimens ( p < 0.05). These results are consistent with the findings of Kang et al [ 32 ]. With Maxcem Elite, HE specimens showed a markedly (810%) higher adhesive strength than CT specimens, as well as a 105% higher adhesive strength than SB specimens.…”
Section: Discussionsupporting
confidence: 94%
“…In this experiment, the zirconia treated by hot etching with two acid solutions was rougher than the sandblasting group, and this experimental finding was consistent with that of Alessio (Casucci et al, 2010). However, the experimental results of You-Jung (Kang et al, 2020) were different. He found that the surface roughness of the zirconia treated with HF hot etching was less than that of the sandblasting group.…”
Section: Surface Roughness (Ra) Valuessupporting
confidence: 78%
“…In recent years, many scholars have begun to try to use HF for the hot etching of zirconia. Kang (Kang et al, 2020) treated zirconia with 9.5% HF at 100 °Cfor 10 min and found that the bond strength of zirconia in this group was significantly higher than that in other groups. Therefore, 37% HCl and 9.5% HF were selected to treat zirconia in this experiment.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Similar to the report of Kang et al . [ 28 ] using Al 2 O 3 , in this experiment, the experimental group treated with air-borne abrasion containing SiO 2 showed significantly higher phase transformation than all the experimental groups treated with HF.…”
Section: Discussionmentioning
confidence: 72%